37 Using research poems to share experiences of having a complex health condition. (22nd November 2019) - Livermore, Polly; Wedderburn, Lucy; Gibson, Faith
Abstract : Objectives: Juvenile Dermatomyositis (JDM) is a rare, complex rheumatological condition with potentially life-threatening consequences and no known cure. This study is the first to ask children and young people to talk about their experience of having this disease; how they feel about their condition, how they live with it day-to-day and what their psychosocial needs are. Presented here are some of their experiences, told using their words, through the medium of poetry. Methods: Data were obtained from 15 young people with JDM, between eight and 19 years of age from one tertiary institution's Paediatric Rheumatology department using audio-taped interviews. Data were analysed phenomenologically, using a process that derives narratives from transcripts resulting in a phenomenon which is evident in the experiences shared. During this process, the words of the young people were shaped into 'research poems' which illustrate the emotions and experience of children and young people living with JDM. Results: Fifteen stories were crafted from interview data, with one phenomenon and five shared narratives for each of the five themes identified. Twelve individual poems were constructed with titles which reflect these shared experiences, such as 'Tomato face'. Conclusion: Whilst poetry was not planned from the outset, in hindsight, the benefits it has brought to this study have been invaluable. The poems are presented as a powerful method of sharing real life voices from young people themselves. Through dissemination, it is hoped that they will aid clinicians to gain a deeper understanding of what daily life is like for these young people, and to consider the impact JDM has, not only on the physical health, but more importantly, the impact on a young person's psychological well-being.